2019
DOI: 10.1108/hff-06-2018-0327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-uniform asymmetric heating on the thermal and entropy generation characteristics for flow of Al2O3-water nanofluid in a micro-channel

Abstract: Purpose The purpose of this study is to numerically analyze the thermal and entropy generation characteristics on two-dimensional, incompressible, laminar single-phase flow of Al2O3-water nanofluid in a micro-channel subjected to asymmetric sinusoidal wall heating with varying amplitude, length of fluctuation period and phase difference of applied heat flux for Reynolds number in the range of 25-1000. Design/methodology/approach The numerical computation is based on the Finite Element Method and the Lagrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The normalized average Nusselt number ( normalNuavg*true) and the normalized total entropy generation ( NS,t*true) versus NPs concentration for the different studied heat flux profile cases and different Ra are presented in Figure 6. This result is interesting, as it allows choosing the conditions giving a higher rate of heat transfer with minimum energy loss (Sheikholeslami et al , 2018b, 2018a, 2019; Boruah et al , 2019; Armaghani et al , 2018; Rashidi et al , 2017). Similar trends have been observed by Abu-Nada et al (2010).…”
Section: Resultsmentioning
confidence: 99%
“…The normalized average Nusselt number ( normalNuavg*true) and the normalized total entropy generation ( NS,t*true) versus NPs concentration for the different studied heat flux profile cases and different Ra are presented in Figure 6. This result is interesting, as it allows choosing the conditions giving a higher rate of heat transfer with minimum energy loss (Sheikholeslami et al , 2018b, 2018a, 2019; Boruah et al , 2019; Armaghani et al , 2018; Rashidi et al , 2017). Similar trends have been observed by Abu-Nada et al (2010).…”
Section: Resultsmentioning
confidence: 99%
“…Taking advantage of the symmetry, a quarter of the rectangular channel as shown in Figure 1 b is chosen as the numerical model to reduce computation cost. The nanofluid can be treated as incompressible Newtonian fluid and the thermophysical properties are assumed to be constant in this study [ 70 , 71 ]. The dimensions of the computational domain in this work are presented in Table 1 .…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Selimefendigil and Oztop (2018a, 2018b, 2018c, 2018d) concluded that adding nanoparticles to the base fluid results in higher heat transfer enhancements for flow over a backward facing step having an elastic bottom wall. Hayat et al (2015), Heydari and Shokouhmand (2017) and Boruah et al (2019) observed the advantageous behavior of nanofluids in attaining higher rates of heat transfer. A detailed review mentioning the recent advancements in modeling and simulation of nanofluid flows was presented by Mahian et al (2018a, 2018b) in two parts.…”
Section: Introductionmentioning
confidence: 99%